ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PADA PERUSAHAAN SAWIT DI INDONESIA - Rosari, Novika; Nailiah, Rusma; Oktaviani, Ayu; Wahyu (JWM (JURNAL WAWASAN MANAJEMEN), 2024)
This research aims to explore the impact of Profitability, Company Size, Leverage and Sales Growth on Profit Management in Palm Oil Companies. The method used in this research is Weighted Least Square using IBM SPSS as the application. Data collection techniques are carried out through documentation methods. The data used in this research is secondary data obtained from the Indonesian Stock Exchange or related company internet sites. The research sample consists of 12 companies listed on the Indonesia Stock Exchange during the period 2017 to 2021. The research results show that the variables Profitability and Leverage have a significant negative influence on Profit Management, while Company size and Sales Growth do not have a significant influence on Profit Management.